Analisis Validitas Pengembangan Media Puzzle Berbasis Puzzlemake A match pada Sub Pokok Bahasan Sel - Nurul Hidayah; Supiana Dian Nurtjahyani (Universitas Sebelas Maret, 2017)
Learning media is an integral part of teaching and learning process to achieve learning objectives. Teachers are required to be able to choose and use the learning media. However, teachers often choose less appropriate learning media. Learning can take place effectively, efficiently and attractively, if a teacher can make changes in delivering the subject matter. Learning media that has been applied by teachers is less fun that makes students become bored and less able to absorb the material taught, so that activity decreases and student learning outcomes become low. This study aims to analyze the level of validity of media experts and material experts to media based puzzle puzzlemake a match on sub cell subject that has been developed through the validity test. Development of this media use ADDIE learning model (Analyze, Design, Development, Implementation, and Evaluation). Data collection techniques use a sheet of validation of media experts and materials. Test of media validity of make-match puzzle based media by media expert and material expert of validity result shows that the level of validity of make-match based puzzle that has been developed reaches 73,82% from facet of valid category media and 87,38% in terms of material expert Category is very valid with the average validity of media experts and material experts reached 80.6% it shows that the validity level of make-match media based puzzle as a learning medium is valid and ready to be utilized in actual learning activities. Based on the results of the research, the learning media based on puzzlemake a match puzzle based on the sub-subject of the developed cell is declared valid to be applied as a learning medium.